Influencing Factors of Shear Instability Characteristics of Rock Joints: Experimental and Theoretical Study - Hangyu Dong; Baohua Guo; Qing Ma; Kai Si; Hongjian Wang (Applied Sciences)
To investigate the influencing factors of the shear failure behavior of rock joints, especially the shear instability characteristics, direct shear tests were performed on marble joints with various grain sizes under different constant normal loads (CNLs). The experimental results show that the grain size and CNL have significant effects on the shear mechanical properties of rock joints. The peak shear strength (τp), peak shear displacement (up), post-peak modulus (S), and stress drop (Δτ) of rock joints all increase first and then decrease with the increase in grain size, but they increase with the increase in CNL. The mineral composition and microstructure also have a certain influence on the shear mechanical properties of rock joints. In addition, the post-peak soften modulus (Sp) was proposed to describe the shear instability characteristics of rock joints, and its relationship with grain size and CNL was established. The mechanical model of the shear instability of rock joints was established, and the shear instability criterion of rock joints was proposed based on the stiffness criterion and the proposed post-peak soften modulus (Sp). This paper further reveals the shear instability mechanism of rock joints, which can provide a reference for the stability analysis of jointed rockmass.